2021
DOI: 10.20944/preprints202109.0426.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploratory Study on Application of MALDI-TOF-MS to Detect SARS-CoV-2 Infection in Human Saliva

Abstract: SARS-CoV-2 caused a large outbreak since its emergence in December 2019. The COVID-19 diagnosis became a priority to isolate and treat infected individuals in order to break the contamination chain. Currently, the reference test for COVID-19 diagnosis is the molecular detection (RT-qPCR) of the virus from nasopharyngeal swab (NPS) samples. Although this sensitive and specific test remains the gold standard, it has several limitations, such as the invasive collection method, the relative high cost and the durat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The combination of ML with MALDI-TOF analysis was also tested on clinical saliva samples (105 positive samples and 51 negative samples). Costa et al 163 compared the classification parameters from 5 ML models to the training dataset and found that the SVM with linear kernel (LK) model with 85.2% accuracy, 85.1% sensitivity and 85.3% specificity provided the best results. The authors used an independent dataset for validation, which was measured at 3 time points after sampling: D0, D10 and D30.…”
Section: Rt-qpcr Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of ML with MALDI-TOF analysis was also tested on clinical saliva samples (105 positive samples and 51 negative samples). Costa et al 163 compared the classification parameters from 5 ML models to the training dataset and found that the SVM with linear kernel (LK) model with 85.2% accuracy, 85.1% sensitivity and 85.3% specificity provided the best results. The authors used an independent dataset for validation, which was measured at 3 time points after sampling: D0, D10 and D30.…”
Section: Rt-qpcr Detectionmentioning
confidence: 99%
“…Particularly due to its discovered advantages over conventional methods, these diagnostic alternatives deserve further development because they could significantly improve the currently available methods. At present, artificial intelligence methods using statistical strategies to recognize statistically significant m/z values ( protein/ peptide patterns) in positive and negative samples appear to be the most promising approach for SARS-CoV-2 diagnostics by MALDI-TOF MS. 5,17,19,162,163 These strategies do not require the identification of specific biomarkers (corresponding to found m/z values), which simplifies the laboratory work and shortens the analysis time. The obtained m/z values can be identified later, e.g., by LC-MS/MS.…”
Section: Future Perspectivesmentioning
confidence: 99%